Research of PTEN mutation in glioma stem/progenitor cells - Yao⁃dong ZHAO; Quan⁃bin ZHANG; Mei⁃qing LOU; Qiang HUANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2010)
Objective More and more attention has been given to the presumption that glioma stem cells (GSCs) originate from neural stem cells (NSCs) with gene mutation, however, there is no enough evidence by now. This paper aims to get evidence of this area. Methods Glioma stem/progenitor cells (GSPCs) and neural stem/progenitor cells (NSPCs) were cultivated in vitro, and were identified before the following studies. Total RNA was isolated and then reverse⁃transcribed into cDNA, with primers specific to phosphatase and tensin homolog deleted onchromosome ten (PTEN), high⁃fidelity Taq polymerase was used for the polymerase chain reaction (PCR) to avoid the incorporation of pseudomutation. After amplification, 10 μl of the reaction mixture was electrophoresed through 1.5% agarose gel, and the rest of the reaction mixture was used for sequencing in both directions. The procedures for the isolation of total RNA to PCR and sequencing were repeated twice, and the sequencing results of both DNA and PTEN peptide chain were analysed with DNAssist 1.0 software and compared to the sequence of wild⁃type Homo Sapiens PTEN in GenBank. Results No mutation happened in the PTEN of NSPCs, but there were many base mutations in the mRNA of PTEN of GSPCs compared with the wild⁃type Homo Sapiens PTEN. Though most of these mutations were same sense mutation, still several mutations were not, including the normal DNA bases of PTEN bases 22 to 42 "ATCGTTAGCAGAAACAAAAGG" in first exon mutated into "CTACGATTGATTTGCATCTTT", base 712 "T" in exon 7 mutated into "C", and base 1192 "A" in exon 9 mutated into "T". Accordingly, for the amino acids (AA) sequence in the peptide chain of PTEN, the mutation included AA from the 8th to the 14th (from "IVSRNKR" to "LRLICIF"), the 238th AA (from "F" to "L"), and the 398th AA (from "T" to "S"). These mutated regions were involved in membrane interaction, particularly the combination with phosphatidylinositol 4, 5⁃biphosphate (PIP2) and maintaining the protein stability of PTEN. Therefore, these mutations not only lead to the rapid degradation of PTEN, but also hinder the cellular function of PTEN to down⁃regulate phosphoinostide 3⁃kinase (PI3K) signaling. Conclusion The mutation of PTEN occurs even in the early stage of malignant transformation, which is probably an initiating agent for the tumorigenesis of gliomas.